Analysis of factors that influence adaptive performance at PT XYZ - Saskia Putri, Raditya; Ardi, Ardi; Sunarjo, Richard Andre (Institute of Computer Science (IOCS), 2024)
Technological advancements have ushered in transformative changes in industrial competition and work methodologies, significantly impacting employees who must adapt to these shifts. This study investigates the dynamics of perceived organizational support, job crafting, and job burnout, exploring their collective influence on adaptive performance with work engagement as a mediating factor at PT XYZ. The quantitative research, encompassing 40 employees at PT XYZ, employs the SEM-PLS analysis technique. The findings affirm the acceptance of all hypotheses, underscoring the substantial impact of job crafting, job burnout, and work engagement on adaptive performance. Equally noteworthy is the confirmed significant influence of perceived organizational support on job crafting, job burnout, and work engagement. This intricate interplay of variables unravels essential insights into the organizational dynamics at PT XYZ, shedding light on strategies to enhance employee adaptability and overall performance. In conclusion, this research not only validates the interconnected influence of perceived organizational support, job crafting, and job burnout on adaptive performance but also underscores the mediating role of work engagement. These insights contribute to the understanding of organizational behavior, offering practical implications for cultivating a positive work culture that fosters adaptability and employee effectiveness, particularly in the ever-evolving landscape of technological advancements at PT XYZ.